Multiple-emitter geolocation by exploiting receiver antenna spatial diversity - Liu, Yakun. (2013)
In this report, the geo-location problem of multiple uncorrelated signal sources from power measurements of a single antenna under translational movement was addressed. In particular, a geo-location scenario was considered in which the signal sources were located within a bounded region-of-interest (ROI) while the directional receiver was collecting the spatial diversity through a vector of received power measurements along each of the three predefined trajectories outside the ROI. Based on the fact that an antenna pattern is band-limited and can be modeled as a function of directivity, the direction-of-arrival (DOA) can be estimated through an annihilating filter method. We first remodeled the antenna pattern into a function of translational movement parameter x. Then Cadzow denoising was utilized to minimize the effect of noise. The x-coordinate estimation could be derived from the annihilating filter method. The complete 2D position estimation was attained by transforming all the x-coordinate estimations of different coordinate systems into the same one, so as to obtain the intersection points of the x-coordinate estimation lines. Eventually the 2D coordinates were revealed by selecting the correct points from the intersection points. The simulation results show a good performance of the proposed approach and the result of this project will be submitted for publication as a journal paper with more analysis on the results.